Formation of tubular carbonate conduits at Athina mud volcano, eastern Mediterranean Sea. (September 2019) - Tamborrino, Leonardo; Himmler, Tobias; Elvert, Marcus; Conti, Stefano; Gualtieri, Alessandro F.; Fontana, Daniela; Bohrmann, Gerhard
Abstract: Tubular carbonate conduits (TCC) represent the termination of fluid plumbing systems in environments of hydrocarbon seepage and play a relevant role in the discharge of methane from sub-seafloor sediments to the water column. However, the biogeochemical reactions and biological activities involved in their formation are not fully understood. To address this, TCC samples were collected with a remotely operated vehicle from the seabed on the SW flank of the Athina mud volcano in the eastern Mediterranean Sea. Petrographic, mineralogical, stable carbon and oxygen isotope and lipid biomarker analyses were performed to elucidate the formation processes of the tubular carbonates. Clotted and fibrous aragonite form the internal lining of the cavities, while the outer portion of the tubes is formed by micritic Mg-calcite cementing hemipelagic sediment. 13 C-depleted Mg-calcite and aragonite (as low as −14.4‰ V-PDB) and lipid biomarkers (archaeol, −89.8‰ V-PDB) indicate that carbonate precipitation was influenced by sulfate-dependent anaerobic oxidation of methane (AOM). AOM locally enhances aragonite precipitation, thereby facilitating early lithification of the conduits within the mud volcano sediments. The size and morphology of the TCC comparable with the buried portion of tubeworm colonies found in the proximity of the sampling site. However, our results suggest that TCC likely formed by the action of burrowing organism rather than being mineralizations of the tubeworm colonies. This study provides new insights into the interpretation and understanding of TCC, highlighting the role of macrofaunal activity in the formation of migration pathways for hydrocarbon-rich fluids on the flank of a mud volcano. Highlights: Carbonate conduits are composed of authigenic 13 C-depleted Mg-calcite and aragonite. Lipid biomarkers reveal involvement of AOM consortia in carbonate precipitation. AOM-induced early lithification of burrows forms tubular carbonate conduits.